Strategic Technology Adaptation Framework: AI, IoT, and the Shift in Strategic Paradigms - Munara, Kasra Jaru; Kamil, Upik Sitti Aslia; Rizki, Muhammad; Pahala, Indra; Handaru, Agung Wahyu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The rapid evolution of strategic technologies such as Artificial Intelligence (AI) and the Internet of Things (IoT) has triggered a paradigm shift in how organizations formulate, implement, and adapt their strategies. However, the current literature on integrating these technologies with the dynamic capabilities framework remains fragmented. This study proposes the Strategic Technology Adaptation Framework (STAF) to conceptually bridge AI/IoT adoption with organizational sensing, seizing, and transforming capabilities. Employing a Systematic Literature Review (SLR) of 30 selected articles published between 2012 and 2024, this research maps the relationships between specific technologies and organizational capabilities across sectors. The study reveals that AI predominantly supports seizing and transforming capabilities through automation and predictive analytics, while IoT enhances sensing through real-time data integration. The proposed STAF model contributes to the dynamic capabilities theory by integrating technological foresight and strategic alignment. It also provides practical guidance for organizations seeking to build adaptive responses and strategic agility in disruptive environments. This study concludes by proposing future empirical validation of STAF through case studies and mixed-method approaches.